Innate Immune Cells in Immune Tolerance After Liver Transplantation - Huang, Hongting; Lu, Yefeng; Zhou, Tao; Gu, Guangxiang; Xia, Qiang (Frontiers in Immunology, 2018)
Abstract: Currently, liver transplantation is the most effective treatment for end-stage liver disease. Immunosuppressive agents are required to be taken after the operations, which have significantly reduced rejection rates and improved the short term (<1 year) survival rates. However, post-transplant complications related to the immunosuppressive therapy have led to the development of new protocols aimed at protecting renal function, preventing de novo cancer and dysmetabolic syndrome. Donor specific immune tolerance, which means the mature immune systems of recipients will not attack the grafts under the conditions without any immunosuppression therapies, is considered the optimal state after liver transplantation. There have been studies shown that some patients can reach this immune tolerance state after liver transplantation. The intrahepatic immune system is quite different from that in other solid organs, especially the innate immune system. It contains a variety of liver specific cells, such as liver-derived dendritic cells, Kupffer cells, liver sinusoidal endothelial cells, liver-derived NK cells, NKT cells and so on. Depending on their specific structures and functions, these intrahepatic innate immune cells play important roles in the development of intrahepatic immune tolerance. In this article, in order to have a deeper understanding of the tolerogenic functions of liver, we summarized the molecular mechanisms of immune tolerance induced by intrahepatic innate immune cells after liver transplantation.